(3JYdjb Ydi QSGdI GdCSQGQ GdecfjIs ((3YHO GdQMef s)
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdYdje hHYO abO hbaJ Ydi gPg GdQSGdI GdJj gH dRdaI GdCHUGQg hgj GdQSGdI GdeSeGI HGdGSQGQ GdecfjI aj GdOhGA GdeYQha HGdcfjI cjfI s
(3BNQgG (B:s
(3LhGgQ WjHGJ aj GdSQ cGfJ eUhfI GfJgj ef NW GdTjN GdHGQY ZHO GdQMef GdLGeY dg s
(3Vef eLehY , JQJjHgG (B: 6s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs